IDDF2018-ABS-0095 The social epidemiological factors linked with intestinal protozoa infection in depok, east java, indonesia. (June 2018) - Simadibrata, Daniel Martin; Alvonico, Timotius; Abdullah, Murdani; Syam, Ari Fahrial; Kurniawan, Agnes; Makmun, Dadang
Abstract : Background: Intestinal protozoa infection consists of infection from Giardia lamblia and Blastocystis hominis . The occurrence is linked with poor personal hygiene, poor sanitation facilities and low education level. Previous studies have reported inconsistent results regarding the prevalence of intestinal protozoa infection. However, the prevalence of intestinal protozoa infection in the urban area of Indonesia has yet to be performed. Therefore, the aim of this study was to determine the prevalence of intestinal protozoa infections in urban region of Indonesia and the contributing sociodemographic factors. Methods: A cross-sectional study was performed among 278 healthy inhabitants in Depok from January to March 2012. Screening for protozoa infection was done through stool sample analysis, in which positive results are indicated by finding cysts or trophozoites. Results: Among the 278 subjects, the overall prevalence of protozoa infections was 12.59%, 88.57% of which was due to Blastocystis hominis . The sociodemographic factor that is significantly associated with the occurrence of intestinal protozoa infection was low BMI level. The normal BMI and obese BMI subjects were at a 0.417 and 0.174 risk of presenting with protozoa infection, respectively, compared to low BMI. The underlying mechanisms include increased bowel permeability and impairment of bowel barrier function, lower IgA antibody level, and villous atrophy. Conclusions: Low BMI level was correlated with increased prevalence of protozoa infection in urban region of Indonesia, Depok.